Cardiogenic syncopal states in children and adolescents - S.Yu. Tereshchenko (Вопросы современной педиатрии)
The article analyzes modern data on diagnostic approaches in children and adolescents with cardiogenic syncopal status. Clinical symptoms of vasovagal attack and common diagnostic algorithm of episode of syncope in children and adolescents are briefly described. Author pays attention to the main cardiac causes of syncope related to organic pathology of a heart and primary disorders of heart rate. The complex of clinical symptoms and signs from medical history is proposed as a predictor of high risk of cardiac origin of syncope; main methods of functional diagnostics in probable cardiogenic syncopal states in children and adolescents are discussed.Key words: children, adolescents, syncope, diagnostics.